Group Theoretic Study of Brenke Type Polynomials - Bajracharya, Shanti (Tribhuvan University Journal, 2010)
Not available. Key words: Brenke; Polynomials <!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–> Tribhuvan University Journal Vol. XIX, No. 2, 1996 Page: 11-23 Uploaded Date: 29 October, 2010